Evaluation of hypolipidemic, antidiabetic and anti-oxidant activity of Eulophia herbacea tubers (Bangladesh Journal of Pharmacology, 2013)
The tuber of Eulophia herbacea is widely used in the treatment of obesity in traditional medicine. Methanolic extract, aqueous extract and isolated glucomannan were tested for triton WR-1339 induced hyperlipidemia and alloxan-induced diabetes in rats. Blood samples were collected and analysed for lipid profile and blood glucose. Glucomannan was isolated and characterised. Anti-oxidant activity of test sample was determined by superoxide radical and lipid peroxidation assay and compared it with standards ascorbic acid. The findings showed that folk medicinal claim of E. herbacea tubers possess hypolipidemic, hypoglycemic and anti-oxidant effects.